Drug induced mucosal erythema multiforme - Gosavi, Anil P.; Jogi, Minal G.; Chavan, Ravindranath B.; Tolat, Sunil N.; Ramawanshi, Smrutirama M. (International Journal of Research in Dermatology, 2018)
Erythema multiforme (EM) is a hypersensitivity reaction to different antigenic stimuli, commoner being infection followed by drugs. It occurs predominantly in younger age group. EM has benign course but frequent recurrences are common especially secondary to HSV infection. Erythema multiforme present as classical cutaneous target/ targetoid lesions and mucosal bullae/erosions. Though almost 70% of patients suffer from mucosal involvement, isolated mucosal affection is very rare. Fuchs syndrome/ectodermosis pluriorificialis is a rare variant characterized by severe involvement of two or three mucosal sites in the absence of skin lesions commonly triggered by Mycoplasma pneumoniae. Here we are reporting a rare case of mucosal erythema multiforme secondary to drug and highlighting the importance of distinguishing it from other similarly presenting mucosal disorders.